THE ATTITUDE OF THE CHRISTIAN DEMOCRATIC POLITICAL PARTY VMRO DPMNE TOWARDS ITS MEMBERS OF THE MUSLIM FAITH (Религиски дијалог и соработка, 2025)
Macedonia is living the fourth decade of its independence, building a new political system,different from the previous one. The new political system rests on democratic values, in an ageof neoliberal pluralism. The new political system builds а mosaic of multi-ethnicity and multi-confessionalism.Political parties are the key factor within the political system, in which citizens organizeand articulate their political participation. It is easier for the Macedonian left, represented bythe political party SDSM, to accommodate the new situation as former communists and atheistsand to nurture contemporary multiconfessionalism. The challenge is for the right, representedby the VMRO DPMNE political party, which from its establishment to the last Congress of 2021,its first ideological determinant was Christian democracy. Given that Macedonia is a multiethnicand multiconfessional environment, the parties are striving for their representativeness. Electionanalysis shows that the right is present in environments with Muslim faith. Further in the compositionof the parliamentary caucus or mayors, the establishment of citizens with Muslim faith inthe VMRO DPMNE party may be observed. It can be assumed that the Christian Democrats haveMuslim members. A real sociological challenge is to investigate the attitude of this party towardsits members of the Muslim faith, how it approaches and mobilizes them. As well as analyzingMuslim members’ attachment to the party, what their motives for membership are, how they areorganized within the party, what common beliefs or values they share. An examination of this interrelationmay provide the answer, why this party after 30 years of its existence and profiling asa Christian democratic party, at the last Congress in 2021, adopted a doctrine in which it profileditself as a people’s party.